DATA FROM CLINICAL AND INSTRUMENTAL EXAMINATIONS OF PATIENTS WITH CHRONIC PAIN IN THE SHOULDER JOINT - V. A. Nesterenko; A. E. Karateev; M. A. Makarov; E. I. Byalik; S. A. Makarov; V. E. Byalik; M. R. Nurmukhametov; A. A. Roskidailo; I. A. Fedotov (Научно-практическая ревматология)
Chronic shoulder pain (CSP) is one of the most common reasons for seeking medical care. Identifying the specific cause of CSP is necessary to determine the treatment strategy.Objective: to determine which pathology of the musculoskeletal system is the main cause of CSP.Subjects and methods. A study group consisted of 151 patients (49.7% females; mean age, 49.8±18.8 years), who experienced shoulder joint pain that persisted when taking nonsteroidal anti-inflammatory drugs (NSAIDs) and after local administration of glucocorticoids. They underwent clinical and instrumental studies (radiography, magnetic resonance imaging, and ultrasound). The investigators assessed pain intensity using a visual analogue scale (VAS), and functional impairment with the American Shoulder and Elbow Surgeons (ASES) Assessment Scores and the Constant Score (CS).Results and discussion. The mean CSP intensity at rest and during movement was 56.1±21.7 and 67.3±19.1 mm VAS. The degree of functional disorders was 55.5±17.6 ASES scores and 54.1±14.5 CS scores. Tendonitis that is an injury to the tendon of the supraspinatus muscle (74.8%) was most common. There was shoulder osteoarthritis (OA) in 31.7%, acromioclavicular (AC) OA in 19.2%, rotator cuff tendon injury concurrent with shoulder OA in 25.2%, that with AC OA in 16.6%, and that with shoulder OA and AC OA in 9.2%. The intensity of pain with only rotator cuff tendon injury and that  concurrent with shoulder OA and/or AC OA did not differ and that averaged 57.2±20.2 and 54.6±18.6 mm at rest, respectively, and 68.3±22.4 and 65.4±19.2 mm during movement (p>0.05 in both cases).Conclusion. The main cause of CSP is tendonitis of the rotator cuff, primarily of the supraspinatus muscle. Moreover, more than half of patients have rotator cuff tendon injury concurrent with biceps tendon injury, shoulder OA and/or AC OA.